The Ancestors of Christ windows at Canterbury Cathedral : [... in conjunction with the Exhibition Canterbury and St. Albans: Treasures from Church and Cloister, on view at the J. Paul Getty Museum at the Getty Center, Los Angeles, from September 20, 2013, to February 2, 2014, and a display of the Ancestors of Christ windows ... at the Cloisters, from February 25 to May 28, 2014] (Getty publications, 2013)
"Discusses the original context, iconographic program, and stylistic development of the Ancestors of Christ windows, which survive from the twelfth century and are significant examples of English medieval painting and monumental stained glass"--Provided by publisher